PERANCANGAN RUMAH SUSUN SEDERHANA SEWA (RUSUNAWA)KOTA GORONTALO DENGAN PENDEKATAN ARSITEKTUR PERILAKU - Pratama Putra, Moh. Noval; Banteng, Beby S.D; Pahrun, Apriyanto A. (Program Vokasi Universitas Negeri Gorontalo, 2023)
Population density in Indonesia is still a serious problem that has not been resolved to date. migration and urbanization carried out by people from year to year which has an impact on the density of urban areas in certain areas. Seeing that the current condition of the city is no longer possible to build large houses for those who live in urban areas, this is the main reason why it is important to design simple rental flats (Rusunawa) in Gorontalo City using a behavioral architecture approach. The methods used in this research are planning, design and descriptive methods. The sample in this research is site analysis, building plan concepts based on real field data taken from survey samples. The result of this design is the arrangement of outdoor space and spatial planning on the basis of behavior. Simple Rental Flats in Gorontalo City are designed to reduce the negative impact of the spread of slum settlements, changing people's lifestyles is important in environmental planning in Gorontalo City. The main objective of the research on the Rusunawa design itself is to produce housing that accommodates the lives of people with below average economic standards and improves the living environment of the city of Gorontalo which is becoming increasingly slum as time goes by.